Investigation of the evaporation characteristics of a transverse vaporized kerosene jet in supersonic flow. (August 2021) - Yang, Kai; Li, Chen-yang; Pan, Yu; Wang, Zhen-guo; Liu, Chao-yang; Wang, Ning
Abstract: The distribution and evaporation characteristics of a transverse vaporized kerosene jet in supersonic flow were experimentally investigated in a ground direct-connected experimental system. Smear-free and high spatiotemporal resolution images of the jet plume were obtained using the pulsed laser sheet imaging method. The incoming flow had a total pressure of 1.0 MPa, a total temperature of 980 K, and an inlet Mach number of 2.0. The boundary and length of the jet plume were identified using the maximum interclass variance method (Otsu). The experimental results show that the kerosene evaporation process is closely related to the fuel temperature and local flow velocity. The two factors competitively influence the phase distribution in the jet plume, resulting in different evaporation distances in the direction perpendicular to the wall. Under subcritical conditions, the jet penetration depths remain basically constant, while the surface wave structures are distinct on the windward side. The jet of critical-state kerosene exhibits a quasi-gaseous flow structure in the near field and undergoes a complex phase transition of secondary condensation and secondary evaporation. According to the different phase states and evaporation degrees, the jet plume is divided into three evaporation regions, providing a complete description of the evaporation characteristics of kerosene at different temperatures in supersonic flow. Highlights: High spatiotemporal resolution images of transverse kerosene jets in supersonic flow were obtained. The couple effect of fuel temperature and local flow velocity on kerosene evaporation was found and analyzed. The influences of injection temperature on penetration depth and evaporation distance were investigated.